2017
DOI: 10.1148/radiol.2017162424
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Screening US–detected Breast Masses by Combined Use of Elastography and Color Doppler US with B-Mode US in Women with Dense Breasts: A Multicenter Prospective Study

Abstract: Purpose To investigate the value of the combined use of elastography and color Doppler ultrasonography (US) with B-mode US for evaluation of screening US-detected breast masses in women with dense breasts. Materials and Methods This prospective, multicenter study included asymptomatic women with dense breasts who were referred for screening US between November 2013 and December 2014. Eligible women had a newly detected breast mass at conventional B-mode US screening, for which elastography and color Doppler US… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
40
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 34 publications
2
40
0
1
Order By: Relevance
“…Previous studies have reported an increase in accuracy when combining B-mode US and ES [19][20]. A previous study reported that the addition of elastography and color Doppler US to B-mode US in dense breasts increased the AUC to 0.96 and specificity to 76.4% without loss of sensitivity [10]. In this study, similarly, the highest AUC and specificity of US were achieved when elastography was added to conventional US for diagnosing breast cancer in dense breasts.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Previous studies have reported an increase in accuracy when combining B-mode US and ES [19][20]. A previous study reported that the addition of elastography and color Doppler US to B-mode US in dense breasts increased the AUC to 0.96 and specificity to 76.4% without loss of sensitivity [10]. In this study, similarly, the highest AUC and specificity of US were achieved when elastography was added to conventional US for diagnosing breast cancer in dense breasts.…”
Section: Discussionsupporting
confidence: 64%
“…However, its average specificity is relatively low and varies according to the tumor indications [9]. A previous study performed in Korea showed that the addition of elastography and color Doppler US to B-mode US can increase the PPV of screening US in women with dense breasts [10]. However, they did not include MRI information and failed to compare the diagnostic value of US and MRI for lesions in dense breasts.…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of the above mentioned criteria the calculated sensitivity, specificity, accuracy, PPV, NPV of DS were 93.3%, 81.5%, 87.7%, 84.8% and 91.7% respectively (Tables 9 and 10). When comparing between Bmode US and DS most studies have reported better specificity for DS and higher sensitivity for B-mode US (Table 10) which is similar to this study results [7,8,15,16]. The lower specificity of B-mode US compared to DS in this study was due to a total of 12 (44.4%) false positive cases ( Table 8).…”
Section: Discussionsupporting
confidence: 84%
“…CDS is a modern technique which increases the diagnostic confidence by showing vascularity in breast tumors [3][4][5][6]. By adding color Doppler signal better characterization of breast mass is possible specially for those mass with BIRADS category 3 and 4 on B-mode US [4,7,8]. Although tumor vascularization is becoming highly important in diagnostic, and prognostic terms, there have always been controversies in different studies to define acceptable criteria for differentiating benign and malignant breast lesions by CDS [3,9].…”
Section: Introductionmentioning
confidence: 99%
“…Shear-wave elastography (SWE) can quantitatively calculate the elasticity parameters of target lesions and provide values, such as mean, minimum, and maximum stiffness; standard deviation of elasticity; and elasticity ratio of breast lesions to the adjacent fat tissue. It is helpful in distinguishing breast cancerous lesions because malignant tissues tend to have increased stiffness compared with benign tissues [8][9][10][11][12]. Also, SWE well predicted the histological upgrade to invasive cancer in ductal carcinoma in situ confirmed at biopsy and response to neoadjuvant chemotherapy in breast cancer [13,14].…”
Section: Introductionmentioning
confidence: 99%